Sistem Pakar Penentuan Jenis Makanan Sesuai Kebutuhan Kalori Pasien Menggunakan Metode Forward Chaining (Studi Kasus : RSUD dr. HA Habibie) - Pratama, Chatra Widsam; Nugroho, Adi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The application of technology in the healthcare industry is increasingly expanding. One of the technological applications that has developed is the application for determining the type of food for hospital patients. In hospitals, patients require special care, including appropriate nutrition. This application provides a solution for determining the type of food that is suitable for the nutritional and health needs of each patient. In determining the food menu, this application uses the forward chaining method that starts from a set of facts and finds rules that fit the hypothesis towards a conclusion. In the process of determining the appropriate type of food for patients, this application considers the unique characteristics of each patient such as gender, age, weight and height, daily activities, and health conditions. With this application, it is hoped that patients in hospitals can obtain the necessary and appropriate nutrition for their bodies, which will ultimately improve their recovery and health process